Molecular profiling and gene expression analysis in cutaneous sarcoidosis: The role of interleukin-12, interleukin-23, and the T-helper 17 pathway - Judson, Marc A.; Marchell, Richard M.; Mascelli, MaryAnn; Piantone, Alexa; Barnathan, Elliot S.; Petty, Kevin J.; Chen, Dion; Fan, Hongtao; Grund, Heidi; Ma, Keying; Baribaud, Frédéric; Brodmerkel, Carrie (Journal of the American Academy of Dermatology, 2012)
Cutaneous sarcoidosis (CS) skin provides relatively noninvasive access to granulomatous sarcoidosis tissue. We sought to explore the role of the T-helper (Th)1 and Th17 pathways in sarcoidosis. We used molecular profiling and gene expression analysis to analyze the Th1 and Th17 pathways and other immune-mediated pathways in CS. Molecular profiles were obtained from sarcoidosis skin lesions (lesional skin [LS]), unaffected skin from patients with CS (non-LS), and the skin of healthy control subjects. Whole blood was collected to compare the molecular profile of sarcoidosis skin lesions and whole blood. Twenty participants were enrolled: 15 with active CS and 5 healthy volunteers. Microarray analyses comparing non-LS and healthy volunteer skin with LS showed several thousand genes differentially expressed (≥2-fold change false discovery rate, P < .01). Targeted selections of genes associated with Th1 and Th17 phenotypes showed a strong Th1 profile of sarcoidosis and expression of interleukin (IL)-23 and IL-23R with limited expression of other Th17 pathway genes. IL-21 and signal transducer and activator of transcription 3 (STAT3) were also dysregulated in skin and whole blood, providing additional evidence for involvement of the IL-12 pathway and potential activation of the Th17 pathway. Measurements were made at a single point in time and may not identify mechanisms that may be identified in patients followed up longitudinally. These findings provide novel insight into the dysregulated pathways that may be involved in the pathogenesis of sarcoidosis.